1996
DOI: 10.1210/jcem.81.9.8784078
|View full text |Cite
|
Sign up to set email alerts
|

The human genome contains only two CYP11B (P450c11) genes.

Abstract: The biosynthesis of glucocorticoids and mineralocorticoids requires isozymes of P450c11. Two human isozymes are known: P450c11 beta, encoded by the CYP11B1 gene, has 11 beta-hydroxylase activity; P450c11AS, encoded by the CYP11B2 gene, has 11 beta-hydroxylase, 18-hydroxylase, and aldosterone synthase activities. Recent data show that the rat genome has four CYP11B genes, three of which are functional, and one of which has novel behaviors. As the number of human CYP11B genes was unknown and as the existence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Alternatively, the disorder could be due to mutation of another gene. However, it has been shown that the human genome contains only two CYP11B genes (18). Thus, we conclude that the endocrine abnormalities of patient 1 are not likely to be caused by genetic variants of the CYP11B2 gene.…”
Section: European Journal Of Endocrinology (1998) 139mentioning
confidence: 57%
“…Alternatively, the disorder could be due to mutation of another gene. However, it has been shown that the human genome contains only two CYP11B genes (18). Thus, we conclude that the endocrine abnormalities of patient 1 are not likely to be caused by genetic variants of the CYP11B2 gene.…”
Section: European Journal Of Endocrinology (1998) 139mentioning
confidence: 57%
“…(1995) suggested the existence of P450c11B3‐like enzyme in patients with corticosterone methyl oxidase type II (COMII) deficiency. However, Zhang & Miller (1996) have reported that the human genome contains only two CYP11B (P450c11) genes. Thus, it is not certain that P450c11β can convert 18‐OH‐DOC to 18‐OH‐B and B to 18‐OH‐B in human adrenal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Only two CYP11B genes are found in humans, 37 but rat studies are complicated by the presence of CYP11B3 and CYP11B4. CYP11B4 seems only to be a pseudogene, but CYP11B3 is expressed in the adrenal zona fasciculata-reticularis for a short period after birth and is regulated by ACTH.…”
Section: Corticosteroid Biosynthesis In the Cardiovascular Systemmentioning
confidence: 99%